Synthesis of (Di)thiahelicenes and Dithiophenohelicenes by [2+2+2] Cycloisomerization of Alkynes. Issue 3 (18th February 2022) - Palata, Ondřej; Andronova, Angelina; Šámal, Michal; Nejedlý, Jindřich; Rybáček, Jiří; Buděšínský, Miloš; Bednárová, Lucie; Pospíšil, Lubomír; Císařová, Ivana; Starý, Ivo; Stará, Irena G.
Abstract: A series of inherently chiral (di)thiahelicenes/dithiophenohelicenes containing 5, 6, 9 or 11 (hetero)cycles in their helical backbone with thiophene subunit(s) embedded in it or annulated to its periphery were uniformly synthesized by intramolecular alkyne [2+2+2] cycloisomerization. Their structural, chemical and physicochemical properties such as crystal packing, oxidation, barrier to racemization, spontaneous thin film transformation or electrochemical behavior were studied and compared with the respective properties of the parent all‐carbon helicenes and dibenzohelicenes. Abstract :